Mathematical modeling of folate metabolism. (22nd May 2013) - Panetta, John C.; Paugh, Steven W.; Evans, William E.
Abstract : Folate metabolism is a complex biological process that is influenced by many variables including transporters, cofactors, and enzymes. Mathematical models provide a useful tool to evaluate this complex system and to elucidate hypotheses that would be otherwise untenable to test in vitro or in vivo . Forty years of model development and refinement along with enhancements in technology have led to systematic improvement in our biological understanding of these models. However, increased complexity does not always lead to increased understanding, and a balanced approach to modeling the system is often advantageous. This approach should address questions about sensitivity of the model to variation and incorporate genomic data. The folate model is a useful platform for investigating the effects of antifolates on the folate pathway. The utility of the model is demonstrated through interrogation of drug resistance, drug‐drug interactions, drug selectivity, and drug doses and schedules. Mathematics can be used to create models with the ability to design and improve rationale therapeutic interventions. WIREs Syst Biol Med 2013, 5:603–613. doi: 10.1002/wsbm.1227 This article is categorized under: Models of Systems Properties and Processes > Mechanistic Models Biological Mechanisms > Metabolism Translational, Genomic, and Systems Medicine > Therapeutic Methods